Access Controlled : The Shaping of Power, Rights, and Rule in Cyberspace - Zittrain, Jonathan; Rohozinski, Rafal; Palfrey, John; Deibert, Ronald (Book collections on Project MUSE., 2010)
Internet censorship and surveillance are increasing in democratic countries as well as in authoritarian states. The first-generation controls, typified by China's "Great Firewall," are being replaced by more sophisticated techniques that go beyond mere denial of information and aim to normalize (or even legalize) a climate of control. These next-generation techniques include strategically timed distributed denial-of-service (DDoS) attacks, targeted malware, surveillance at key points of the Internet's infrastructure, take-down notices, and stringent terms-of-usage policies. Their aim is to shape and limit the national information environment. Access Controlled reports on these new trends in information control and their implications for the global internet commons. Access Controlled is a publication of the OpenNet Initiative (ONI), a collaboration of the Citizen Lab at the University of Toronto's Munk Centre for International Studies, Harvard's Berlman Center for Internet & Society, and the SecDev Group (Ottawa), and is an extension of ONI's earlier volume, Access Denied. Six substantial chapters analyzing internet controls worldwide are supplemented by a section of shorter regional reports and country profiles drawn from material gathered by the ONI through a combination of technical interrogations and field research methods. Support for Access Controlled was provided by the Office of the OSCE Representative on Freedom of the Media.